2020
DOI: 10.31128/ajgp-11-19-5148
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of early lung cancer

Abstract: BackgroundLung cancer is the leading cause of cancer death in Australia. Recently there have been unparalleled advances in the screening and management of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…In addition, traditional tumour biomarkers have a low sensitivity for early diagnoses due to the low tumour burden released into peripheral circulation in early-stage lung cancer. 27 We also observed the diagnostic value of these two circRNAs compared with CEA, CYFRA21-1, and SCC. The ROC curves showed that the AUC values of hsa_circ_101555 and hsa_circ_008068 were excellent compared with those of traditional tumour markers for the diagnosis of early LUAD.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, traditional tumour biomarkers have a low sensitivity for early diagnoses due to the low tumour burden released into peripheral circulation in early-stage lung cancer. 27 We also observed the diagnostic value of these two circRNAs compared with CEA, CYFRA21-1, and SCC. The ROC curves showed that the AUC values of hsa_circ_101555 and hsa_circ_008068 were excellent compared with those of traditional tumour markers for the diagnosis of early LUAD.…”
Section: Discussionmentioning
confidence: 69%
“…In recent years, non-tracheal intubation anesthesia has developed rapidly, and preservation of the patient's selfbreathing during thoracoscopic surgery can effectively avoid the occurrence of airway trauma and postoperative complications caused by tracheal intubation (20,21). In our team's previous study (4), performing VATS pneumonectomy under non-intubation anesthesia reduced the intraoperative blood loss, postoperative drainage, postoperative white blood cell and neutrophil proportions, and reduced hospitalization costs. It has been reported that endotracheal intubation can cause sympathetic nerve excitation (22), which leads to increased blood pressure, whereas the non-endotracheal intubation method avoids the pressure effect, and hemodynamics remain more stable.…”
Section: Discussionmentioning
confidence: 96%
“…At present, the preferred method for the early diagnosis and treatment of pulmonary nodules is video-assisted thoracoscopic surgery (VATS) (3). Thoracic pneumonectomy is performed under conventional tracheal intubation anesthesia, but tracheal intubation is an invasive procedure that can damage the trachea, cause postoperative discomfort in the throat of the patient, and also cause damage to the non-ventilated lung (4). Moreover, it requires a large dose of anesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…The lung is an important organ of the human respiratory system, and lung tumor is also directly related to human health. Early surgical planning and treatment can improve the cure rate and increase the survival rate of patients [ 2 , 3 ]. Computer-aided accurate segmentation can effectively assist doctors in surgery planning and treatment decisions [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%